Development and characterization of roselle (Hibiscus sabdariffa L.) nanocellulose-reinforced polylactic acid nanocomposite for water filtration - Lau, Kia Kian (2019)
Roselle is abundantly cultivated in tropical areas, such as Malaysia, Borneo, Indonesia, India, Tanzania, Thailand, Sri Lanka, Sudan, Tanzania, Togo and Guyana. Roselle fiber is a potential bio-filler for composites reinforcement. In Malaysia, the roselle plant is harvested annually for its fruit and the remaining parts, such as the stem are disposed of as agricultural waste. Roselle plant is a valuable source of cellulose. The growing environmental awareness endowed the utilization of nanocellulose as alternative fiber to reinforce biopolymers. This research is to investigate the characterization of isolated microcrystalline cellulose, nanocrystalline cellulose and cellulose nanowhisker from roselle fiber and fabrication of polylactic acid nanocomposites for membrane applications. The isolation of microcrystalline cellulose from roselle fiber was conducted by employing bleaching, alkali treatment and acid hydrolysis. Also, different hydrolysis reaction time and sonication time were used to extract both nanocrystalline cellulose and cellulose nanowhisker from microcrystalline cellulose. Characterization of microcrystalline cellulose (MCC), nanocrystalline cellulose (NCC), and cellulose nanowhisker (CNW) were carried out by using various advance equipments. From the implemented experiment, microcrystalline cellulose exhibited rough surface in the form of microcrystallites with high thermal stability which was contributed by the substantial removal of lignin and other residues. Nanocrystalline cellulose and cellulose nanowhisker possessed dimension in nanometer range in the form of needle-like and elongated rod-like particles shape respectively. The degree of crystallinity has been improving for nanocrystalline cellulose (79.5%) and cellulose nanowhisker (79.9%) after the isolation from microcrystalline cellulose (78.0%). Besides this, the thermal stability is found decreasing for both types of nanocellulose particles which resulted by the presence of sulfur content. At later stage, nanocrystalline cellulose and cellulose nanowhisker were used as reinforcing material to develop polylactic acid (PLA) nanocomposites. Comparison was carried out between nanocrystalline cellulose and cellulose nanowhiskers reinforced polylactic acid nanocomposites to select the suitable membrane for metal ions treatment. As examined from characterization, cellulose nanowhisker filled polylactic acid membranes showed better porous structure than that of nanocrystalline cellulose filled polylactic acid membrane besides its great thermal stability, mechanical strength and metal ions adsorption capability. Ultimately, an improvement is conducted to further enhance the properties of selected nanocellulose reinforced polylactic acid nanocomposite membrane by dual layer fabrication method as well as water vapor-induced phase separation technique. Dual layer membrane filled with 3 wt% cellulose nanowhisker possessed well-laminated two layers structure. The membrane porosity was improved, while the pore size decreased with the increment of nanocellulose loadings from 1 to 3 wt%. This evidenced the nanocellulose acted as pore-forming agents within the membrane. In continuous wastewater filtration, dual layer membrane exhibited high efficiency in removing both Co²⁺ and Ni²⁺ metal ions with 83% and 84%, respectively. Therefore, the experimental settings in this study are believed can be used in future research studies on the isolation and extraction of microcrystalline cellulose, nanocrystalline cellulose and cellulose nanowhisker from roselle fiber as well as the production of good performed roselle nanocellulose reinforced polylactic acid nanocomposite for membrane application.